Trends and variations in the epidemiology of meningococcal disease in Kuwait 1987–2013. Issue 5 (September 2015) - Husain, Entesar H.; Barakat, Mohammad; Al-Saleh, Mosaab
Summary The introduction of Haemophilus influenzae type b (Hib) conjugate vaccine and conjugate pneumococcal vaccine into routine childhood vaccination in Kuwait has resulted in the emergence of Neisseria meningitidis as the leading cause of invasive bacterial infection in children. Currently, a quadrivalent ACYW-135 meningococcal polysaccharide vaccine is administered as part of routine childhood vaccination in Kuwait at the age of 2 years. Conjugate meningococcal vaccines have been shown to be more effective in preventing meningococcal infection in young children. The objective of this study was to describe the epidemiology of meningococcal disease (MD) in Kuwait and evaluate the need for conjugate vaccine in routine childhood immunization. We have reviewed the MD surveillance data from the communicable disease unit, Ministry of Health, Kuwait during the period from 1987 to 2013. The analysis included microbiologically confirmed cases of N. meningitidis in the blood and cerebrospinal fluid. There were 293 cases of confirmed MD during the study period. Two hundred and four cases (70%) were in children ≤14 years of age. The mean incidence rate was 0.5/100, 000 persons. The dominant serogroups were W-135 and B, accounting for 80 cases (32%) each. Serogroup B accounted for 69/204 (34%) of all cases in children ≤14 years and serogroup A accounted for 36/89 40% of all adult cases. There were three outbreaks: 1987 (caused by serogroup A), 1989 (caused by serogroup W-135) and 2002 (caused by serogroup B). The mean case fatality rate was 13.5%. In conclusion, despite childhood routine vaccination with ACYW-135 polysaccharide vaccine, infants and young children remain at high risk for MD, which supports the introduction of conjugate meningococcal vaccine to the routine childhood vaccination schedule.